PREDICTION OF AERODYNAMIC COEFFICIENTS OF MISSILE USING PANEL METHOD (Journal of Engineering, 2006)
The low order panel method with Neumann boundary condition have been used to predict thenormal force curve slope, the pitching moment curve slope, the center of pressure location and theaerodynamic load distribution for missile in compressible, steady flow. The wing-body-canardinterference problem have been solved using two schemes (iterative method and internal singularitymethod) both are based on the panel method. The normal force curve slope, the pitching momentcurve slope and the center of pressure location for a given missile has been predicted using thepresent numerical method and the DATCOM technique.